The realms of rhetoric and grammar / Sick Goh Ngong (Universiti Teknologi MARA, Sarawak, 1992)
This article has been written with special reference to local Chinese writers who use Mandarin as their means of communication. Therefore, direct discourses will be extracted from their writing for illustration and clarification purposes.